The role of soil compaction in ensuring subgrade stability in various climatic conditions (Eurasian Research Bulletin, 2023)
This article presents the results of a study to determine the maximum density and optimal moisture content of soils, taking into account the patterns of the water-thermal regime of the subgrade, the sources of wetting the subgrade and the entire road structure, and their seasonal water-thermal regime.